Modulation strategy of dynamic voltage restorer based on dual-feedforward active disturbance rejection compound controller - Huang, Langchen; Liu, Weiling; Zhang, Ning; Yan, Qingyun; Wei, Xinwei (Frontiers in Energy Research, 2025)
Given the contradiction between compensating speed and compensating overshoot in traditional Proportional Integral (PI) control of Dynamic Voltage Restorer (DVR), A Feedforward compensation-active Disturbance Rejection Control (FC-ADRC) strategy based on Feedforward Compensation is proposed. ADRC control is used to improve the problem of compensating oversets existing in traditional PI control, and the voltage and current of the LC filter are introduced as the feedforward quantity to compensate the DVR controller to realize the rapid voltage compensation for the voltage dip on the user side and ensure the safety and stability of the voltage on the user side. The simulation results show that the proposed control strategy not only keeps the high dynamic response of the DVR device but also ensures the device’s adaptability to deal with uncertain disturbances.